2022
DOI: 10.1186/s12967-022-03657-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification of SSBP1 as a ferroptosis-related biomarker of glioblastoma based on a novel mitochondria-related gene risk model and in vitro experiments

Abstract: Background Glioblastoma (GBM) is the most common primary malignant brain tumor that leads to lethality. Several studies have demonstrated that mitochondria play an important role in GBM and that mitochondria-related genes (MRGs) are potential therapeutic targets. However, the role of MRGs in GBM remains unclear. Methods Differential expression and univariate Cox regression analyses were combined to screen for prognostic differentially-expressed (DE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 77 publications
0
12
0
Order By: Relevance
“…In the mitochondria, SSBP1 is required for regulating mitochondrial function, cell metabolism, and tumorigenesis. [11][12][13][14] Furthermore, SSBP1 mutations impaired mitochondrial DNA maintenance and replication, which was related to optic atrophy, foveopathy, autosomal dominant optic atrophy, and a complex optic atrophy disorder. [15][16][17][18] Recently, it has been reported that the suppression of SSBP1 may be a potential therapy for the treatment of podocyte ferroptosis in glomerular injury.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the mitochondria, SSBP1 is required for regulating mitochondrial function, cell metabolism, and tumorigenesis. [11][12][13][14] Furthermore, SSBP1 mutations impaired mitochondrial DNA maintenance and replication, which was related to optic atrophy, foveopathy, autosomal dominant optic atrophy, and a complex optic atrophy disorder. [15][16][17][18] Recently, it has been reported that the suppression of SSBP1 may be a potential therapy for the treatment of podocyte ferroptosis in glomerular injury.…”
Section: Discussionmentioning
confidence: 99%
“…In the mitochondria, SSBP1 is required for regulating mitochondrial function, cell metabolism, and tumorigenesis 11–14 . Furthermore, SSBP1 mutations impaired mitochondrial DNA maintenance and replication, which was related to optic atrophy, foveopathy, autosomal dominant optic atrophy, and a complex optic atrophy disorder 15–18 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proliferation assessment utilized the Cell Counting Kit-8 (CCK-8) and EdU cell proliferation assays, following manufacturer guidelines [34,35] . Proliferation rates were monitored every 24 hours with a multiscanner autoreader (BioTek, VT, US) and a uorescence microscope (Nikon, Japan).…”
Section: Cell Proliferation Assessmentmentioning
confidence: 99%
“…This, in turn, inhibits the progression and migration of glioblastoma (GBM) cells by enhancing ferroptosis. SSBP1 has been identified as a potential ferroptosis-associated biomarker for GBM ( 97 ).Ferroptosis regulated by mitochondria plays a crucial role in cancer progression ( 98 , 99 ). Recent studies have revealed that cGAS is localized to the outer mitochondrial membrane, where it interacts with dynein-associated protein 1 (DRP1) to promote DRP1 oligomerization.…”
Section: Ferroptosis In Disease Therapy Through Targeting Mitochondrialmentioning
confidence: 99%